Migration of nonylphenol and plasticizers from polyvinyl chloride stretch film into food simulants, rapeseed oil, and foods. Issue 3 (5th July 2016) - Kawamura, Yoko; Ogawa, Yuko; Mutsuga, Motoh
Abstract: Nonylphenol (NP) has been suspected as an endocrine‐disrupting chemical. Japanese polyvinyl chloride (PVC) stretch films contained 0.5–3.3 mg/g of NP and 100–400 mg/g of plasticizers such as diisononyl adipate (DINA), di‐ n ‐alkyl adipate (DAA), and diacetyllauroyl glycerol (DALG). Migration of NP and plasticizers from PVC stretch films into food simulants (water; 4% acetic acid; 20%, 50%, and 95% ethanol; and heptane), rapeseed oil, and foods was investigated. Plasticizers migrated only in small amounts into aqueous simulants and foods, although they migrated at much higher levels into 50% and 95% ethanol, heptane, rapeseed oil, and fatty foods, whereas NP more easily migrated into aqueous simulants and foods. At 5°C for 24 hr, migration of NP into vegetable and fruit was 2.9%–6.4% of their contents, and that of DINA and DAA was 0.1%–0.3%. The migration ratios of NP into aqueous foods were much higher than those of DINA and DAA. The migration ratio of NP into fatty foods, such as minced tuna and pork, was 33% and 24%, which was almost similar to that of DINA and DAA. The estimated daily intakes of NP and DINA for Japanese individuals of those days were 35 and 1, 050 μg, respectively, and should not be associated with any safety concerns. Abstract : Nonylphenol (NP) more easily migrated from polyvinyl chloride (PVC) stretch film into aqueous foods than diisononyl adipate (DINA) and di‐n‐alkyl adipate (DAA). The migration ratio of NP, DINA, and DAA into fatty foods, such as minced tuna and pork, came to 15%–37% of their contents in PVC films at 5°C for 24 hr. The estimated daily intakes of NP and DINA for Japanese individuals around the year 2000 were 35 and 1, 050 µg, respectively, and should be no safety concern.